The Abidah El Khalieqy's Novel Perempuan Berkalung Sorban: A Feminist Analysis - Etty Ani; Sulistyaningsih Sulistyaningsih (JournEEL, 2023)
Abstract In patriarchal countries, women are viewed as belonging to a lower class than men. This study aims to comprehend the feminism used in Perempuan Berkalung Sorban's novel. The goals of this study are to 1) define feminism in Perempuan Berkalung Sorban's novel and 2) comprehend the feminist organisations that are present in the text. This study employed a qualitative descriptive research methodology. According to the research, Perempuan Berkalung Sorban's feminism represents a woman's battle for existence and human rights, and it also contains both liberal and radical feminism. Keyword : right, novel, qualitative descriptive research, feminism